Hungarian Monitoring, 15 May 1990 . [Magyar rádiófigyelő], 1990. május 15 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - On the Soviet-American Foreign Ministers' meeting - Session of the new Ukrainian Parliament - Romania restores full diplomatic relations with the Vatican - Willy Brandt in Prague Domestic Affairs: - Árpád Göncz meets the President of the World Jewish Congress (WJC) in New York - Public debate with János Kis and Imre Pozsgay - Negotiations on the Budapest-Vienna World Exposition - Hungary applies for European Organization for Nuclear Research membership Economy: - Budapest meeting of the International Industrial Union - Hungary to receive USD 500 million bridge loan Külpolitika: - A szovjet-amerikai külügyminiszteri találkozóról - Ülésezik az új ukrán parlament - Helyreálló diplomáciai kapcsolat Románia és a Vatikán között - Willy Brandt Prágában Belpolitika: - Göncz Árpád New Yorkban találkozik a Zsidó Világkongresszus elnökével - Nyilvános vita Kis János és Pozsgay Imre között - Tárgyalás a Budapest-Bécs világkiállításról - Magyarország felvételét kéri az Európai Atomkutató Szervezetbe Gazdaság: - Budapesten tanácskozik a nemzetközi iparunió - 500 millió dollár áthidaló kölcsönt kap Magyarország